PENGARUH METODE STORYTELLING DENGAN MEDIA BONEKA TANGAN TERHADAP PENGETAHUAN KONSUMSI SAYUR ANAK USIA PRASEKOLAH - Dwi Elka Fitri; Awaliyah Ulfah Ayudhyta; Dede Suryadi (Jurnal Ilmu Kesehatan Abdurrab, 2023)
Children's interest in consuming vegetables is still very low and refuses to consume vegetables. Consuming fibrous foods is very good because it can help expedite the digestive process in the body. This can be caused by a lack of ideas to tell, a lack of vocabulary to express ideas, a lack of opportunities to speak, and a lack of interesting teaching methods that can motivate them. Storytelling is a method that is appropriate to cognitive roles and is effective for preschool-aged children. The purpose of this study was to determine the effect of the media storytelling method on knowledge of vegetable consumption in preschool-aged children. This study used a quantitative research method using a quasi-experimental design with the one group pre-posttest model. The respondents of this study were pre-school age children at Munzhirah Kindergarten, Pekanbaru City. The dependent variable in this study is the knowledge of school-age children about vegetable consumption. Sampling is based on the normal distribution with the central limit theorem, amounting to 30 respondents. Data analysis in this study used the paired sample T test. The results showed that a p-value of 0.000 < an alpha value of 0.005 meant that there was an effect of the storytelling method on knowledge of vegetable consumption in pre-school-age children. It is hoped that from the results of this research early childhood education institutions can conduct health education about vegetable consumption in pre-school age children through various interesting methods, such as the storytelling method using hand puppets or other playing methods, so that children can understand and be motivated to consuming vegetables.